But I Still Feel Guilt: A Test of a Moral Disengagement Propensity Model. Issue 3 (8th August 2019) - Kacmar, K. Michele; Carlson, Dawn S.; Thompson, Merideth; Zivnuska, Suzanne
ABSTRACT: We explored the impact of moral disengagement on individual experiences of guilt. We modeled three forms of workplace deviance (withdrawal, interpersonal deviance, and work-family deviance) as mediators between the propensity to morally disengage and guilt, and also includes the moderating effects of perceived work hours culture. Data were collected from 226 employees matched with a colleague and spouse. Results demonstrated that moral disengagement released individuals who engaged in interpersonal and work-family deviance from subsequent feelings of guilt, but only reduced feelings of guilt for those who withdrew. We also found an interactive effect of perceived work hours culture on the relationships between moral disengagement propensity and all three forms of deviance. The indirect effect from moral disengagement propensity to guilt through withdrawal was stronger when perceived work hours was high.